Are Immigrant Remittance Flows a Source of Capital for Development? - Jahjah, Samir; Chami, Ralph; Fullenkamp, Connel (Washington, D.C. : International Monetary Fund, 2003)
The role of remittances in development and economic growth is not well understood. This is partly because the literatures on the causes and effects of remittances remain separate. We develop a framework that links the motivation for remittances with their effect on economic activity. Because remittances take place under asymmetric information and economic uncertainty, there exists a significant moral hazard problem. The implication is that remittances have a negative effect on economic growth. We test this prediction using panel methods on a large sample of countries. The results indicate that remittances do have a negative effect on economic growth, which indicates that the moral hazard problem in remittances is severe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet